Factors that interfer in the quality of service to the critical patient (Acta Scientiarum. Health Sciences, 2020)
The objective was to identify the factors that interfere with the quality of nurses' care to patients in the urgency and emergency service. This is a qualitative, exploratory and descriptive study, conducted in the months of September to November 2017 with 16 nurses, in the critical sectors of a public hospital referral in urgency and emergency in Teresina, Piaui, Brazil. The main factors identified that interfere with the quality of care provided by nurses were: inadequate conditions at work, improper physical structure in meeting high demand from patients, insufficient materials and equipment, dimensioning of inadequate personnel, in addition to a health care network that finds problems to achieve adequate patient flow. It is noted the need to develop institutional programs in the study hospital, in order to value and motivate the assisting professionals, since exposure to constant negative feelings can trigger physical and mental illnesses, in addition to exerting a great influence on the quality of the patients. services that are provided.